Evaluation of human amniotic membrane as a scaffold for periodontal tissue engineering: an in vitro study - Elahi , Asrar (2017)
Human amniotic membrane (HAM) has many biological properties suitable for periodontal tissue regeneration such as low immunogenicity, anti-fibrosis, antiinflammation and rich in extracellular matrix component. This study aimed to evaluate the ability of this membrane as a scaffold for the growth of the predominant cells in periodontal tissues, human periodontal ligament fibroblasts (HPDLFs). Commercially available HPDLFs (Lonza, USA) were seeded on glycerol preserved HAM (USM Tissue Bank, Malaysia). HPDLFs attachment and surface morphology were observed through histological analysis and scanning electron microscopy (SEM) respectively. While the cell proliferation was assessed using alamarBlue® proliferation assay and nuclear labeling of DNA using 6-diamidino-2-phenylindole (DAPI) at day 1, 3, 7, 14 and 21. Histologically, HPDLFs showed mono layer to multilayers attachment on HAM from day 1 to day 7. On day 14 and 21, HPDLFs cell layers were reduced to single cell layer with more flattened appearance and longer spindle shaped cells. SEM analysis demonstrated that HPDLFs had attached appropriately on HAM surface at day 1 to day 3 and became overlapping at day 7, while maintaining their flat shape. However, by day 14 and 21 the cells demonstrated alteration in their morphology and later became rounded in shape. Based on statistical analysis (Friedman’s Two-Way Analysis of Variance by Ranks followed by pairwise comparison) using SPSS 22.0 proliferation assay showed that HPDLFs viability on HAM had increased significantly from day 1 to day 7 (p=0.012).However, the proliferation of cells showed significant reduction at day 14 (p=0.002) and day 21 (p=0.005). DAPI staining of nuclear DNA showed the presence of HPDLFs up to day 7 only. This study showed that HAM is able to function well as a scaffold for HPDLFs within 7 days. Retardation of cellular growth after 7 days could be due to possible reasons such as density dependent inhibition of growth or the release of matrix metalloproteinases by the HPDLFs that might have degraded the membrane. In conclusion, the findings suggest that HAM could be a promising scaffold for periodontal regeneration. However, cells’ behaviour in relation to the membrane over longer culture duration requires further investigations.